Kebermaknaan Konseling Kelompok dalam Menanggulangi Masalah Kehidupan - Hengki Yandri; Gusti Rahayu; Neviyarni Suhaili; Netrawati Netrawati (Institut Agama Islam Negeri Kerinci, Indonesia, 2022)
Every human being must have problems; what distinguishes them is how individuals respond and live them. Hence, it takes someone who is an expert (counsellor) to accompany people experiencing problems (clients) to take on the responsibility of their lives and become happy individuals. Group counselling is one of the services that counsellors can provide to help clients or group members solve their life problems because the purpose of this service is to alleviate client problems by utilizing group dynamics to establish a sense of empathy and mutual understanding and help between fellow group members. In this article, we will discuss in more detail the meaning of group counselling in overcoming human life problems, starting from discussing the meaning of group counselling, the differences between group counselling and individual counselling, the function of group counselling in overcoming life problems, the purpose of holding group counselling, principles of group counselling, and therapy that can be used in group counselling